THE EFFECTS OF SCIENTIFIC-BASED LEARNING STRATEGY (IMAGES MEDIA AND LECTURE METHOD) AND STUDENTS LEARNING MOTIVATION TOWARDS SCIENCE ACHIEVEMENT ON STUDENTS OF CIRUAS 2 ELEMENTARY SCHOOL - Rodiyah Rodiyah; Cecep Anwar Hadi Firdos Santosa; Maman Rumanta (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2020)
This study aims to determine the effects of scientific-based learning strategy (images media and lecture method) and students learning motivation towards the students achievement of learning science. This research applied 2 x 2 factorial design, a type ofquasi-experimental design. Results are as follows: (1) there are differences in the students achievement of learning science between students who are taught using thescientific-basedlearning strategy withimages media and students who are taught usingscientific-basedlearning strategywith lecture method, (2) there are differences in the students achievement of learning science between students who have a strong learning motivation and students who have a weak learning motivation, (3) For students who have a strong learning motivation, whether the students achievement of learning science are higher when taught withscientific-based learning strategywith images media than with the lecture method, (4) For students who have a weak learning motivation, are the results of learning science higher when taught with the scientific-based learning strategy with lecture method compared to thescientific-basedlearning strategy withimages media, (5) there is an interaction between scientific-based learning strategyand students learning motivation towards students achievement of learning science.Keywords: Scientific Based Learning, students learning motivation, students achievement of learning science